Juridical Study of Halal Certification Impact on Entrepreneurial Market Access within the ASEAN Economic Community - Angelita, Elmonita Delima (IHSA Institute, 2024)
This research conducts a juridical study of halal certification within the ASEAN Economic Community (AEC), examining its legal frameworks, economic impacts, challenges, and competitive dynamics. Halal certification plays a pivotal role in protecting entrepreneurs' products within the AEC by ensuring compliance with Islamic dietary laws, building consumer trust, and facilitating market access. However, entrepreneurs encounter challenges such as bureaucratic hurdles, high certification costs, and inconsistencies in standards across countries. Despite these challenges, halal certification has positive impacts on competition within the AEC, including enhanced market access, consumer trust, and competitive differentiation. Nevertheless, potential negatives such as trade barriers, compliance costs, and regulatory fragmentation must be addressed to fully realize the benefits of halal certification. Collaborative efforts among governments, industry stakeholders, and certification bodies are essential to streamline certification processes, harmonize standards, and reduce compliance burdens. By leveraging the benefits of halal certification and addressing its challenges, entrepreneurs can effectively compete in the diverse markets of the AEC, driving economic prosperity and promoting regional integration.